A national health service : draft memorandum on the government's proposals
1944-04-14 1944 1940s 14 pages - 7 - voluntary money, if only for the reason that such a large part of the hospital's voluntary income is derived from local sources. Secondly, the arrangement proposed would remove from the local authority any opportunity - if such were sought - of using the power of the purse to gain control of the voluntary hospitals. 15. - Calculation of Exchequer Payment. It might have been expected that in this Memorandum we should have been prepared to make certain specific suggestions as to the amount of the exchequer payment. It will, however, be appreciated that it is impossible to indicate these figures with any accuracy since it will depend on the extent to which the voluntary hospitals are enabled to continue to rely on annual voluntary support, and such cannot be foreseen with any certainty until more is known of the proposals of the government to ensure the continuance of that support. It should, however, be borne in mind that the level of expenditure upon hospital services is not static and increases year by year. This will be more than ever true in the development of a plan for co-ordination and expansion of hospital services. It follows that there should be machinery to enable the total amount of the exchequer payment to be increased as circumstances may require from time to time. The amount of the total annual exchequer payment should be determined by reference not only to cost or percentage of cost but also to the medical and service requirements of the voluntary hospitals judged in the light of evidence available. The total annual exchequer payment might be fixed for a period of three to five years. Such a plan would afford the necessary measure of stability. A provisional sum would have to be agreed in respect of the initial period. 16. - Contributory Schemes. The foregoing represent the hospitals' comments on the main principles affecting the proposed hospital service. Details have been avoided, although, in addition to the principles referred to, there is much that needs to be clarified before the voluntary hospitals can give full support to the scheme. There is much, too, they world have liked to mention; for instance, no reference has been made to voluntary contributory schemes. The Minister's declaration in the House of Commons that there could be no place for voluntary contributory schemes in the government's proposals for complete social insurance has caused intense disappointment. It still hoped that, if the main principles advocated by the voluntary hospitals are accepted, some means may yet be found whereby such schemes could continue to play a useful part. 17. - Capital Monies. No reference has been made, either, to the question of capital monies required by hospitals for rebuilding and extension purposes. This question is one of paramount importance. We can, however, emphasise that the same principles as apply to payments for maintenance must apply in the case of capital monies; that is to say, they should be made from a central, and not local, funds and available to the voluntary hospitals on the same terms and conditions as may be available to local authorities. SUMMARY. Summarising the foregoing, the voluntary hospitals desire to state that:- (1) Equal representation in the planning and maintenance of the hospital service mast be afforded to the voluntary hospitals. This can only be achieved within the framework of the Scheme by the establishment of a Central Hospitals Board, and Regional and Local Hospitals Councils, as defined. 292/847/2/33